Factors influencing first-service conception and overall pregnancy rates in commercial beef heifers - S.D. Utter; P.L. Houghton; L.R. Corah; D.D. Simms; M.F. Spire; M.D. Butine (Kansas Agricultural Experiment Station Research Reports, 1994)
Commercial beef heifers (n=1863) from 16 different sources were used to evaluate the influence of management practices and biological traits on first-service conception and overall pregnancy rates. Frame score, initial weight, overall ADG, body condition score, reproductive tract score, source, AI technician, and AI sire significantly influenced first-service conception. Overall pregnancy rates were influenced by frame score, body weight, and ADG.
Keywords: Cattlemen' s Day; 1994; Kansas Agricultural Experiment Station contribution; no. 94-373-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 704; Beef; Beef heifers; First-service conception; Pregnancy rates